Analisis Maqashid Syariah Dalam Fatwa DSN-MUI Tentang Akad-Akad Di Perbankan Syariah di Bank Syariah Indonesia Kantor Cabang Tasikmalaya Sutisna Senjaya - Lutfi Ahmad Furqon (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The rapid growth of the Islamic banking industry in Indonesia has encouraged the need for in-depth studies related to the application of Islamic principles in banking practices. Maqashid Syariah, as the goal of Islamic law, is an important reference in the development of Islamic banking products and services. The Fatwa of the National Sharia Council-Majelis Ulama Indonesia (DSN-MUI) plays a central role in providing guidance for the Islamic banking industry. Therefore, this study aims to analyze the extent to which the concept of Maqashid Syariah has been implemented in the DSN-MUI fatwas related to Islamic banking contracts, especially in Mudharabah, Murabahah, and Rahn. (1) to analyze how the concept of Maqashid Syariah is reflected in the fatwas of DSN-MUI regarding Islamic banking contracts. (2) to measure the level of harmony between the DSN-MUI fatwas on the three contracts with the principles of Maqashid Syariah; and (3) to identify the implications of the application of Maqashid Syariah in the fatwas on Islamic banking practices at Bank Syariah Indonesia Sutisna Senjaya Tasikmalaya Branch Office. This research uses a qualitative method with a content analysis approach to the relevant DSN-MUI fatwas. In addition, in-depth interviews were also conducted with the bank to obtain a more comprehensive understanding of the implementation of Maqashid Syariah in Islamic banking practices. The case study was conducted at Bank Syariah Indonesia Sutisna Senjaya Tasikmalaya Branch Office. The results show that the DSN-MUI fatwas have consistently referred to the five elements of Maqashid Sharia, namely protecting religion, soul, mind, offspring, and property. The implication is that the fatwas have provided a strong foundation for Islamic banking practices that are oriented towards the benefit of the people. The application of Maqashid Syariah in DSN-MUI fatwas and Islamic banking practices at Bank Syariah Indonesia Sutisna Senjaya Tasikmalaya Branch Office has significant implications.